HUBUNGAN ANTARA PENEBALAN ENDOMETRIUM PADA PEMERIKSAAN ULTRASONOGRAFI TRANSVAGINAL DENGAN PEMBERIAN TERAPI TAMOXIFEN TERHADAP PENDERITA KANKER PAYUDARA - MARINA, TINA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Introduction: Estrogen Receptor (ER) positive breast cancer sufferer mostly using Tamoxifen hormonal therapy. Tamoxifen is a selective estrogen receptor modulator drug whose pharmacological profile is estrogen antagonist on some body tissue, while to some other tissue act as estrogen agonist. In the breast tissue, Tamoxifen act as estrogen antagonist that inhibit the binding of estrogen to the estrogen receptor. Hence it inhibits breast tissue cells proliferation. In the endometrium, Tamoxifen may has estrogen-like effect or agonist characteristic. It can trigger endometrium cells proliferation and cause endometrial thickening. Purpose: The purpose of this study is to determine the correlation between the increase in the frequency of the occurrence of endometrial thickening on transvaginal ultrasound (US) examination with Tamoxifen therapy of patients with breast carcinoma . Materials and Methods: This is a cross-sectional non-experimental study with consecutive non random sampling technique. Measuring instruments used were questionnaires and imaging of transvaginal gray-scale US examination of the endometrium. Analysis of the statistical test used was Fisher's exact test. Results:The most age group when diagnosis of breast carcinoma established is 41-50 years old, 15(46,9%) women in the Tamoxifen group, and 14(48,3%) women on control group. There is significant mean difference of endometrial thickness in premenopause subject between Tamoxifen group than those with no Tamoxifen (p=0,029). The mean use of Tamoxifen was 17,6 months. There are only 5(7,8%) women which have endometrial thickening in this study, 3(9,4%) women on Tamoxifen group and 2(6,3%) women on control group, with no significant correlation statistically (p=1,000). Conclusion: There is no significant correlation (p=1,000) between the endometrial thickening occurrence on transvaginal US examination with Tamoxifen therapy of breast carcinoma patients. Key words: breast carcinoma, Tamoxifen, endometrial thickening, ultrasound examination.